2009
DOI: 10.1128/aem.00201-09
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal Diversity and the Prevalence of Crenarchaeota in Salt Marsh Sediments

Abstract: Crenarchaeal 16S rRNA sequences constituted over 70% of the archaeal clones recovered from three salt marsh sites dominated by different grasses. Group I.1a Crenarchaeota dominated at two sites, while group I.3b Crenarchaeota sequences were most abundant at a third site. Abundances of 16S rRNA genes related to "Candidatus Nitrosopumilus maritimus" differed by site and sampling date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 19 publications
3
23
0
2
Order By: Relevance
“…The high abundance of ammonia-oxidizing archaea (∼50%) within the archaea in this soil, as visualized by fluorescence microscopy, also was confirmed by qPCR of amoA and 16S rRNA genes. Because ammonia-oxidizing archaea such as Nitrosopumilus maritimus are thought to harbor only one copy of the 16S rRNA gene and only one copy of the amoA gene, the gene copy numbers derived by qPCR should be equivalent to cell numbers (34,35). We also analyzed the archaeal 16S rRNA transcripts from light and heavy fractions of RNA-SIP and observed a close relation to Nitrososphaera gargensis.…”
Section: Discussionmentioning
confidence: 94%
“…The high abundance of ammonia-oxidizing archaea (∼50%) within the archaea in this soil, as visualized by fluorescence microscopy, also was confirmed by qPCR of amoA and 16S rRNA genes. Because ammonia-oxidizing archaea such as Nitrosopumilus maritimus are thought to harbor only one copy of the 16S rRNA gene and only one copy of the amoA gene, the gene copy numbers derived by qPCR should be equivalent to cell numbers (34,35). We also analyzed the archaeal 16S rRNA transcripts from light and heavy fractions of RNA-SIP and observed a close relation to Nitrososphaera gargensis.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, Mosier and Francis, (2008) found that copies of b-proteobacterial amoA were two orders of magnitude higher than archaeal amoA in high-salinity estuarine sediments. In salt marshes specifically, a report from southeastern Connecticut found a high abundance of 16S rRNA genes related to the ammonia-oxidizing 'Candidatus Nitrosopumilus maritimus' isolate (Nelson et al, 2009). Thus, although the study here focuses solely on AOB, further study on AOA is needed to expand the picture of the salt marsh nitrifying community.…”
Section: Introductionmentioning
confidence: 90%
“…Overall, these results provide strong evidence for niche partitioning among the AOA in the water column and brine pools of the Red Sea. Moreover, a large number of environmental sequences that cluster with the Nitrosopumilus cluster were retrieved from habitats with a broad salinity range (5-33% (w/v)), or replete with ammonium (0.1-2 mM) and sulfate (0.1-701 mM; Yakimov et al, 2007;Nelson et al, 2009;Swan et al, 2010;Park et al, 2010;La Cono et al, 2011), which implies a broader halotolerance and greater tolerance for ammonium in some species of this genus.…”
Section: G I 1 a -A S S O C Ia T E D M G I 1 B E U R Y A R C H A mentioning
confidence: 99%